Intervensi Analisis Lirik: Mengatasi Ruminasi Kognitif Remaja Akhir Perempuan dengan Lirik Lagu BTS - Ernestine Oktaviana Yuniswara; Nurul Hartini (Airlangga University Press, Universitas Airlangga, 2022)
The tendency toward cognitive rumination among females in their late adolescence was increasing during the COVID-19 pandemic, which in turn may lead to the development of anxiety and depression disorders. Lyrics Analysis Intervention in group aiming to redirect thoughts and introduce more effective coping mechanisms is one of the methods in Cognitive Behavioral Therapy to overcome cognitive rumination. In this report, the characteristic shared by the intervention group members as a fan of the South Korean boy band, BTS (Bangtansonyeondan), was used as a basis of the song selection. Discussing the song